Improving Students’ English Vocabulary Mastery by Using Canva Animation for the Fifth Grade Students at SDN 1 Martapura - Al Fahri; Nurhasanah; Henny Yulia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja, 2024)
This study aimed to improve the English vocabulary mastery of fifth-grade students at SDN 1 Martapura by using Canva animation as a teaching medium. Vocabulary mastery is essential for language learning; however, many elementary students struggle with conventional methods. This research applied a pre-experimental design with a one-group pre-test and post-test model. The sample comprised 27 fifth-grade students selected through cluster random sampling. The treatment involved animated videos created with Canva focusing on vocabulary related to professions and workplaces. Data were collected using multiple-choice and matching tests, then analyzed using a paired sample t-test in SPSS. Findings revealed a significant improvement in students’ vocabulary mastery, with mean scores increasing from 66.26 (pre-test) to 81.59 (post-test). The significance value was 0.000 (<0.05), indicating that Canva animation effectively enhanced students’ vocabulary acquisition. This study concludes that Canva animation provides an engaging and interactive learning experience that positively impacts young learners' vocabulary skills.